1991
DOI: 10.1039/c39910001691
|View full text |Cite
|
Sign up to set email alerts
|

Amperometric biosensor based on direct communication between glucose oxidase and a conducting polymer inside the pores of a filtration membrane

Abstract: Please be advised that this information was generated on 2018-05-12 and may be subject to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…At higher potential the de pendence is less dramatic. In accordance with previous results [14,16,27] we found that at a potential of 100 mV versus Ag/AgCl reference the current due to the addition of glucose still resulted in a positive current response, whereas the deliberate addition of a small amount of hydrogen peroxide (0.0025 wt.%) resulted in a strongly negative response [28][29][30]. This experiment shows that the response to glucose must be the result of direct electronic contact between the enzyme mol ecules and the conducting polymer indicating that ox ygen mediation is not an important mechanism (see also below).…”
Section: Amperometric Measurementssupporting
confidence: 82%
“…At higher potential the de pendence is less dramatic. In accordance with previous results [14,16,27] we found that at a potential of 100 mV versus Ag/AgCl reference the current due to the addition of glucose still resulted in a positive current response, whereas the deliberate addition of a small amount of hydrogen peroxide (0.0025 wt.%) resulted in a strongly negative response [28][29][30]. This experiment shows that the response to glucose must be the result of direct electronic contact between the enzyme mol ecules and the conducting polymer indicating that ox ygen mediation is not an important mechanism (see also below).…”
Section: Amperometric Measurementssupporting
confidence: 82%
“…Chemical template synthesis can be accomplished by simply immersing the membrane into a solution of the desired monomer and its oxidizing agent (7,11,33). Such methods have since been used by other groups (34)(35)(36)(37).…”
Section: Template Synthesis Of Conductive Polymersmentioning
confidence: 99%
“…For example, recent work has shown that FADH 2 can give its electrons directly to the doped form of polypyrrole; i.e. a mediator is not necessary (30). We have recently developed an interfacial polymerization method to synthesize ultrathin film composite membranes based on polypyrrole and its derivatives (3).…”
Section: Resultsmentioning
confidence: 99%